Polypurine/polypyrimidine hairpins form a triple helix structure at low pH. - Mooren, M M (1990)
1D and 2D NMR investigations of the 15 residue deoxynucleotide sequence d(TCTCTC-TTT-GAGAGA) show that above pH = 6.5 the molecule adopts a B-form hairpin conformation. As the pH is lowered below 6.5 molecules progressively associate in pairs to form a partially triple helical, partially single stranded structure in which the bases of the oligopyrimidine d(TC)3 tract from one molecule form Hoogsteen pairs with the d(G-A)3 tract of the other. Imino protons of protonated cytosines can be observed at very low field (approximately 15 ppm). The enthalpy of triplex formation was estimated by NMR techniques to be -16 kcal mol-1. Intense H6 to H3' cross peaks from residues in all three strands suggest the presence of N-type sugars at some but not at all possible sites. Surprisingly strong cross peaks between H5' or H5" and non-exchangeable base protons are also observed. These suggest that certain of the O5'-C5'-C4'-C3' phosphate backbone torsion angles (gamma) are unusual.